STABILITAS STRUKTUR TANAH CANDI SUKUH: SAAT INI DAN MENDATANG - Hendi Soesilo (Balai Arkeologi Yogyakarta, 2016)
The research of soil structure stability at Sukuh Temple was carried out in order to seek the answer to geotechnical and geological issues of the temple’s environment. This National Heritage Site, which,was built around 14th century AD,has some environment disturbances caused by developing settlement area, tourism, and mining. Furthermore, theexistence of mining activity at the site as shown by the tunnels and caves in the underground of the Temple’s area, could makepotentiall triggers for landslide in the future of the temple. Considering the major influence of mining activity in the area of this site, the soil structure study is necessery for focusing to assess the threats caused by this mining activity in the Temple’s area. Geotechnical survey and geological survey condition have been done to collect data for this study. The survey were also been done for identifying other aspect such as earthquake in surrounding area of the Temple.